Pendampingan Pengimplementasian Gerakan Literasi Sekolah Di SMPN 25 Kota Malang - Iswatiningsih, Daroe; Pangesti, Fida (Universitas Nusantara PGRI Kediri, 2020)
The Science and Technology Program for the Community aims to provide assistance in implementing the school literacy movement at SMPN 25 Malang. The target of this activity is the principal and all teachers of Malang City Public Middle School 25, but the next stage is focused on the literacy team of Malang City Public Middle School. The method applied is a workshop and assistance. The results of this activity were in the form of a manual for the literacy movement of the 25th Junior High School in Malang, which consisted of (a) the School Literacy Movement in the Junior High School, (b) the Literacy Activity Program of the 25th Junior High School in Malang, (c) closing. In addition, SMPN 25 Kota Malang has implemented 3 of the 8 planned programs.